Relationships between Body Weight Perception and Weight Management: Practices among Adolescents - Dhungel, Kshitiz Upadhyay; Bhattarai, Barsha (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Overweight and obesity are highly prevalent in western countries and growing problems in developing countries. Weight loss behaviors are highly prevalent among adolescents, and body weight perception motivates weight control practices. The aim of this study is to investigate the relationships between actual body weight, body weight perception, and weight control practices among adolescents.Material and methods: A questionnaire-based survey was used to collect data on anthropometric measurements, demographic information, weight perception and weight control practices from a sample of 200 male and female students (89 boys and 111 girls) aged between13 and19 year old. The association between weight loss attempts and socio demographic factors, weight status and the weight perception were analyzed. Multivariable logistic regression analyses were performed to examine the predictors of misperception and its association with weight-related behaviors. Cohen's kappa was calculated to analyze the accuracy of body weight perceptions.Results: This study revealed that prevalence of underweight was higher in girls than boys. In this study, 8% were underweight including 3.5% severely underweight, 23.5% were overweight, 6% were obese and the rest of the participants (59%) were of normal weight. Only 61.5% respondents perceived their weight correctly. Perception of 21.5% adolescents was underestimated and 16.5% were overestimated than their actual weight status. Almost one third of the respondents were in weight control interventions. Almost 11% boys and 33% girls attempted weight loss activities. The gender biasness was seen in weight control (statistically significant ,p value =0.003). Body weight perception was found significant (p value, 0.001) in relation to weight control behavior.Conclusion: Body weight perceptions are not in agreement with actual weight in adolescents. This discrepancy is more marked in females who use a variety of weight control behaviors. These behaviors are motivated more apparently by perceived weight rather than actual body mass index.